Analisa Prestasi Berbicara Siswa di Kampung Inggris PALI - Wati, Indah (Politeknik Pariwisata Medan, 2024)
English as a global language is taught to the students as the subjects in primary schools to universities. Alongside with that circumstances, students also could learn from informal places, like English course or Online Platform, that create various opportunities for students to learn English. Kampung Inggris PALI is one of the informal place to learn English at PALI, that can infiltrate the Language Teaching at the informal classroom direcly and to formal classroom indirectly with the output of the concept is the more motivated student to learn to speak English, that not too many formal and informal institution can offer. Students’ speaking achievement at Kampung Inggris PALI were analyzed by using some techniques: observation, interview, and document analysis. The qualitative method was used in this research. The results indicate that the students in Kampung Inggris PALI have strong motivation in speaking English although they still have lack in grammar, vocabulary and pronunciation, fluency and English Understanding